L2 Acquisition at the interfaces: Subject-verb inversion in L2 English and its pedagogical implications - Teixeira, Joana Alexandra Vaz (2018)
The present PhD thesis deals with two kinds of interfaces that have recently become key areas of interest in generative second language acquisition research (GenSLA): (i) linguistic interfaces – the syntax-discourse interface (our main focus of research) and the lexicon-syntax interface in adult second language (L2) acquisition –, and (ii) an interdisciplinary interface – the interface between the domains of GenSLA and L2 pedagogy. The thesis seeks to shed new light on four general questions which are still a matter of debate in GenSLA: (i) Are narrow syntactic and lexical-syntactic properties unproblematic at the end state of L2 acquisition, as the Interface Hypothesis (IH) (Sorace & Filiaci, 2006; Sorace, 2011b) predicts? (ii) Are properties at the syntax-discourse interface necessarily problematic at the end state of L2 acquisition, as the IH proposes? (iii) What are the roles of cross-linguistic influence, input and processing factors in L2 acquisition at the syntax-discourse interface? (iv) Can explicit instruction help L2 learners/speakers (L2ers) overcome persistent problems in the acquisition of syntactic and syntax-discourse properties? With a view to investigating these questions, the thesis focuses on a linguistic phenomenon that has been little researched in GenSLA: subject-verb inversion (SVI) in L2 English. Three types of SVI are considered here: (i) “free” inversion (and their correlation with null subjects), (ii) locative inversion and (iii) presentational there-constructions (i.e., there-constructions with verbs other than be). The first is ungrammatical in English due to a purely syntactic factor: this language fixes the null subject parameter at a negative value. The last two types of SVI, on the other hand, are possible in English under certain lexical, syntactic and discourse conditions. The thesis comprises two experimental studies: (i) a study on the acquisition of the lexical, syntactic and discourse properties of SVI by advanced and near-native L2ers of English who are native speakers of French (a language similar to English in the relevant respects) and European Portuguese (a language different from English in the relevant respects), and (ii) a study on the impact of explicit grammar instruction on the acquisition of “narrow” syntactic and syntax-discourse properties of SVI by intermediate and low advanced Portuguese L2ers of English. The former study tests participants by means of three types of tasks: untimed drag-and-drop tasks, syntactic priming tasks, and speeded acceptability judgement tasks. Their results confirm that, as predicted by the IH, the properties of SVI that are purely (lexical-)syntactic are unproblematic at the end state of L2 acquisition, but those which involve the interface between syntax and discourse are a locus of permanent optionality, even when the first language (L1) is similar to the L2. Results are, moreover, consistent with the prediction of the IH that the optionality found at the syntax-discourse interface is primarily caused by processing inefficiencies associated with bilingualism. In addition to presenting new experimental evidence in favour of the IH, this study reveals that the degree of optionality L2ers exhibit at the syntax-discourse interface is moderated by the following variables, which have not been (sufficiently) considered in previous work on the IH: (i) construction frequency (very rare construction → more optionality), (ii) the quantity and/or distance of the pieces of contextual information the speaker needs to process (many pieces of contextual information in an inter-sentential context → more optionality), (iii) the level of proficiency in the L2 (lower level of proficiency → more optionality), and (iv) the (dis)similarity between the L1 and the L2 (L1≠L2 → more optionality). The study which concentrates on the impact of explicit grammar instruction on L2 acquisition follows a pre-test, treatment, post-test and delayed post-test design and tests participants by means of speeded acceptability judgement tasks. This study shows that explicit grammar instruction results in durable gains for L2ers, but its effectiveness is moderated by two factors: (i) the type of linguistic domain(s) involved in the target structure and (ii) whether or not L2ers are developmentally ready to acquire the target structure. Regarding factor (i), research findings indicate that the area that has been found to be a locus of permanent optionality in L2 acquisition – the syntax-discourse interface – is much less permeable to instructional effects than “narrow” syntax. Regarding factor (ii), results suggest that explicit instruction only benefits acquisition when L2ers are developmentally ready to acquire the target property. As these findings are relevant not only to GenSLA theory, but also to L2 teaching, the thesis includes an analysis of the relevance and potential implications of its findings for L2 grammar teaching.